2017
DOI: 10.1093/brain/awx001
|View full text |Cite
|
Sign up to set email alerts
|

Improving working memory performance in brain-injured patients using hypnotic suggestion

Abstract: Working memory impairment is prevalent in brain injured patients across lesion aetiologies and severities. Unfortunately, rehabilitation efforts for this impairment have hitherto yielded small or no effects. Here we show in a randomized actively controlled trial that working memory performance can be effectively restored by suggesting to hypnotized patients that they have regained their pre-injury level of working memory functioning. Following four 1-h sessions, 27 patients had a medium-sized improvement relat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(52 citation statements)
references
References 42 publications
4
48
0
Order By: Relevance
“…However, this literature also has some methodological shortcomings (Lindeløv et al, in review). A randomized controlled study found very large and persistent improvements on working memory (all d > 1.4) following four and eight hours of hypnosis (Lindeløv et al, 2017). A further analysis of interview data from this study found a one-hour reduction in the median need for daily sleep as well as progress on 75% of patientreported outcome measures (Lindeløv et al, in review).…”
Section: Hypnosis and Brain Injury: Four Cases And Three Predictionsmentioning
confidence: 53%
See 4 more Smart Citations
“…However, this literature also has some methodological shortcomings (Lindeløv et al, in review). A randomized controlled study found very large and persistent improvements on working memory (all d > 1.4) following four and eight hours of hypnosis (Lindeløv et al, 2017). A further analysis of interview data from this study found a one-hour reduction in the median need for daily sleep as well as progress on 75% of patientreported outcome measures (Lindeløv et al, in review).…”
Section: Hypnosis and Brain Injury: Four Cases And Three Predictionsmentioning
confidence: 53%
“…We have received similar reports from around a third of the participants in Lindeløv et al (2017). Most participants report immediate improvement, but were later surprised to learn that the improvement was much larger than initially felt.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations